Clinical Implication of Caloric and Video Head Impulse Tests for Patients With Enlarged Vestibular Aqueduct Presenting With Vertigo - Li, Ming; Leng, Yangming; Liu, Bo (Frontiers in Neurology, 2021)
Background: By examining the clinical features and results of video head impulse test (vHIT) and caloric tests in patients with enlarged vestibular aqueduct (EVA) presenting with vertigo, we aimed to investigate the function of angular vestibulo-ocular reflex (VOR) and its clinical implications. Methods: Nine patients with EVA manifesting with vertigo were enrolled. The medical history, audiological examination, imaging, and the results of the caloric test and the vHIT were analyzed. Results: Of the nine patients with EVA (eight bilateral and one unilateral case), five were pediatric cases. All 17 ears exhibited sensorineural hearing loss (SNHL). Enlarged vestibular aqueduct patients can present with recurrent (seven cases) or single (two cases) vertigo attack, trauma-induced (two cases), or spontaneous (seven cases) vertigo. Diminished caloric responses were observed in 77.8% (7/9) of the patients (four cases unilaterally and three bilaterally), while unilateral abnormal vHIT results in 11.1% (1/9) patients. Abnormal caloric and normal horizontal vHIT responses were found in 66.7% (6/9) of EVA patients. Conclusions: Vestibular manifestations in EVA are diverse. Enlarged vestibular aqueduct patients with vertigo can present with a reduced caloric response and normal horizontal vHIT, and this pattern of angular VOR impairment was also found in other hydropic ear diseases.